Assessment of Ground Water Recharge through Mathematical Modeling in Wagarwadi Watershed in Parbhani District, M.S. - Gore, K.P.; Pendke, M.S.; Jadhav, S.N. (Journal of Soil and Water Conservation, 2022)
Wagarwadi watershed (324 hectares) is a micro-watershed of Purna river located in Parbhani District. Maharashtra. A ground water flow model of the micro-watershed was constructed to assess the impact of impounded water in nala bunds on the groundwater regime. The water table configuration of June 1997 was assumed to be under equilibrium and was considered as initial water level for steady stare condition. The permiability was estimated from two pumping tests and is found ’varying from 1 to 1.6 m/day. Ground water recharge was estimated as 91.21 mm from a separate %cater balance model during 1997-98. A specific yield of 0.001 was arrived from the wells assigned appropriately in the model. The recharge contribution from impounded water in two nala builds and cement plug structures have been simulated as lake interaction in the model. The hydraulic conductance of 20 m2/day for nalabunds and 10 m2/day for cement plug ponds -Was simulated in the model. Maximum rise of ’water table of 2 m has been observed in wells located about 200 m on the downword slope of nala blind no. 2. There has been an overall increase in water table elevation owing to artificial recharge from impounded water in the water harvesting structures. The artificial recharge has beet: worked out as 8274 M3 for nala bund no. 1, 18083 1113 for nala bund no. 2 and 4452 m1 for cement plug. The contribution amounts to 36.7%, 49.6% and 64.7% of corresponding surface water impoundment under nala bund no. 1, nala bund no. 2 and cement plug no. 1, respectively during the year. The nala bunds and cement plug structures were found effectively contributing for artificial recharge through harvested water in the Wagarwadi watershed. The quantification of additional recharge arrived through ground water modeling study will help to assess the efficiency of the water harvesting structures in enhancing the ground water potential.